Character Concretization Through Boarding School Culture: Case Studi In Padang Lawas Utara District - Salminawati Salminawati; Zulhedd Zulhedd; Apniar Apniar (Institut Agama Islam An-Nawawi Purworejo, 2023)
This research examines the concretization of the character of the santri through culture at the North Padang Lawas Islamic Boarding School which was formed through a continuous process of pesantren education so that it is firmly rooted in the identity of the santri. The approach used in this research is a case study at Islamic boarding schools in North Padang Lawas Regency. Sources of data were taken through primary data sources, namely asatidz administrators, students, and secondary sources obtained from documents and images related to research. Researchers as actors. As for data collection techniques through observation, interviews, and documentation. The results of the study show that: (1) The character building of the students at the North Padang Lawas Regency Islamic Boarding School is through education in the yellow book, educational habits, educational advice, attention to education and education through activities in the Islamic boarding school. (2) Centric character is formed through the culture of the pesantren at the North Padang Lawas Regency Islamic Boarding School, namely caring for the environment, hard work, cooperation, responsibility, togetherness, creativity, confidence, cohesiveness, caring, mutual cooperation, solidarity, tolerance, vulnerability, honesty, curiosity, respecting the opinions of others, mutual respect, tolerance, not arrogant, accepting what is, caring, discipline, not wasting time, diligent, tenacious, humble, maintain behavior.